Characterizations of Continuous Fractional Bessel Wavelet Transforms - Srivastava H.M.; Mishra K.K.; Upadhyay S.K. (My University, 2025)
In this paper, we present a systematic study of the various characteristics and properties of some continuous and discrete fractional Bessel wavelet transforms. The method is based upon the theory of the fractional Hankel transform. © 2022 by the authors.